Retroperitoneal Spindle Cell Tumor: A Case Report - Hua, Hao; He, Zhiwei; Lei, Linhan; Xie, Huahua; Deng, Zilei; Cheng, Zili; Zuo, Shi; Sun, Chengyi; Yu, Chao (Frontiers in Surgery, 2021)
Spindle cell tumor is very rare. Herein, we report a case of retroperitoneal spindle cell tumor in a 52-year-old female. The patient first presented with a complaint of persistent pain in the right upper abdomen. In the follow-up, a CT scan was performed and showed a retroperitoneal soft tissue density mass measuring 11 cm in diameter. Then, a subsequent operation was performed, and we completely removed the tumor and partially invaded lesions. The tumor was histologically diagnosed as a spindle cell tumor. Therefore, it is imperative for us to enhance the understanding of this seldom found tumor. Surgery remains the best option for treatment.